2023
DOI: 10.1039/d3an01675g
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of small molecule fluorescent probes targeting EGFR for tumor detection and treatment

Depu Song,
Tengli Ding,
Weibin Zhai
et al.

Abstract: Epidermal growth factor receptor (EGFR) is a tyrosine kinase receptor that plays a crucial role in cell differentiation and tumor progression, and its overexpression is closely associated with the development...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Previous reports demonstrated that gefitinib exhibits IC 50 values ranging from ten to tens of micromoles in diverse cell types including breast cancer cells (MCF-7, MDA-MB-231), colon cancer cells (HT-29, HCT-116, CT26), liver cancer (HepG2) and normal cells (HEK-293T). 72 Consistent with these findings, our experimental result also indicated a concentration-dependent inhibition on CT26 tumor cell growth by gefitinib, except at relatively low concentrations where it slightly promoted cell proliferation (Fig. S3A, ESI †).…”
Section: Anti-tumor Effect and Immunoregulatory Activity Of Prophagoc...supporting
confidence: 89%
“…Previous reports demonstrated that gefitinib exhibits IC 50 values ranging from ten to tens of micromoles in diverse cell types including breast cancer cells (MCF-7, MDA-MB-231), colon cancer cells (HT-29, HCT-116, CT26), liver cancer (HepG2) and normal cells (HEK-293T). 72 Consistent with these findings, our experimental result also indicated a concentration-dependent inhibition on CT26 tumor cell growth by gefitinib, except at relatively low concentrations where it slightly promoted cell proliferation (Fig. S3A, ESI †).…”
Section: Anti-tumor Effect and Immunoregulatory Activity Of Prophagoc...supporting
confidence: 89%